Quantification and Statistical Assessment of Lumbar Intervertebral Disc Spaces (Applied Biological Research, 2024)
Lower back pain (LBP) is a prevalent issue affecting the lumbar region of the human body, with degenerative discs identified as a significant contributing factor. X-ray imaging, often the first recommended investigation by Orthopaedic Doctors, offers valuable insights into the condition of the intervertebral discs in the lumbar spine. In this study, intervertebral disc spaces were quantified using image processing techniques and compared the quantified values to established normal ranges. The results revealed significant deviations between the deteriorated intervertebral disc spaces and the mean and standard deviation values of healthy subjects, confirming instances of disc degeneration. Several risk factors were found to influence disc degeneration, including gender, age, and body mass index (BMI). A comprehensive statistical analysis highlighted how these factors, while having small but significant effects, contribute to the overall health of the lumbar spine, providing a clearer understanding of their impact on disc degeneration through robust non-parametric studies.
Keywords: Lower back pain; Quantification; Intervertebral disc spaces; Normality Test; Non-Parametric Test; Mann-Whitney U Test